2020
DOI: 10.3390/ijerph17197024
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Trunk Stabilization Exercise Combined with Vibration for Adolescent Patients with Nonspecific Low Back Pain

Abstract: There are many adolescent patients complaining of low back pain, but research on it is lacking. The purpose of this study was to investigate the effects of trunk stabilization exercise combined with vibration on the pain, proprioception, and kinematics of the lumbar spine (LS) during sit to stand (STS) in adolescent patients with nonspecific low back pain (LBP). Fifty LBP patients were recruited and were randomly divided into two groups: Vibration group (n = 25) and placebo group (n = 25). All participants und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 42 publications
(61 reference statements)
0
27
0
Order By: Relevance
“…The mean age of participants ranged from 12.3 to 18 years old. Among participants in the eight studies reporting sex, 50.4% ( n = 261) were female [ 22 , 32 34 , 37 , 38 , 40 , 41 ]. All studies included participants with nonspecific LBP, with no studies focusing on TSP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mean age of participants ranged from 12.3 to 18 years old. Among participants in the eight studies reporting sex, 50.4% ( n = 261) were female [ 22 , 32 34 , 37 , 38 , 40 , 41 ]. All studies included participants with nonspecific LBP, with no studies focusing on TSP.…”
Section: Resultsmentioning
confidence: 99%
“…All studies included participants with nonspecific LBP, with no studies focusing on TSP. Participants received various rehabilitation interventions including exercise (4 studies) [ 34 36 , 39 , 40 ], spinal manipulation (2 studies) [ 22 , 33 ], cognitive therapy (1 study) [ 38 ], whole-body vibration (1 study) [ 37 ], and multimodal care (2 studies) [ 32 , 41 ]. The duration of rehabilitation interventions varied: 1) four weeks (1 study) [ 22 ]; 2) eight weeks (4 studies) [ 34 36 , 38 , 40 ]; and 3) 12 weeks (4 studies) [ 32 , 33 , 37 , 39 ]; and 4) variable duration (1 study) [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After TrA training, the blood circulation of the waist core muscles is accelerated, which could promote the absorption of pain inflammatory factors [54]. After the pain is reduced, it could promote improvement of waist proprioception [55]. Studies showed that even a small amount of exercise may cause changes in the cerebral cortex and increase motor evoked potentials [56].…”
Section: Discussionmentioning
confidence: 99%